Ambientalização curricular nos cursos de licenciatura da Universidade Federal de Sergipe - Fonseca, Mariana Reis (2021)
This dissertation addresses the context of Curriculum Environmentalization (AC) in undergraduate courses at the Federal University of Sergipe (UFS), with the general objective of elucidating the paths adopted by UFS in the fields of teaching for the implementation of CA in teacher training courses. ), signaling the possibilities and limitations for its effective development. The present work is constituted as a qualitative research, aiming at the process of facing the socio-environmental problems that permeate society. As a research stage for data production, document analysis and semistructured interviews were selected. The sample of this research is composed of managers who make up administrative positions in the teaching area of UFS; and coordinators of courses offered in the face-to-face modality, taking into account the inclusion of the environmental dimension in the Pedagogical Course Projects (PPC) of teacher training courses on the UFS campuses. Based on the information produced, the data were analyzed based on a theoretical framework that encompasses the AC in the perspective of Critical EE as a political act of transforming reality. Thus, for data analysis, the Discursive Textual Analysis (DTA) technique was adopted. The results achieved point to the lack of consistency and consensus regarding environmentalization in the PPC of the courses and among the managers interviewed. The fragmentation of knowledge was the most observed factor in both data collections, reflecting a nonintegrated, discontinued EE approach consistent with the conservationist and pragmatic bias disseminated by the media. Therefore, this research contributed to the understanding and theoretical deepening of how the AC of the undergraduate degrees at UFS has been incorporated into the different proposed educational knowledge and allowed to visualize the importance of a continuing education that approaches the AC in a critical and reflective way with the coordinators. and university professors.